Highly active and selective nickel molybdenum catalysts for direct hydrazine fuel cell. (10th October 2016) - Asset, Tristan; Roy, Aaron; Sakamoto, Tomokazu; Padilla, Monica; Matanovic, Ivana; Artyushkova, Kateryna; Serov, Alexey; Maillard, Frederic; Chatenet, Marian; Asazawa, Koichiro; Tanaka, Hirohisa; Atanassov, Plamen
Abstract: Carbon-supported NiMo catalysts (NiMo/C) were synthesized and investigated for the electrooxidation of hydrazine. Their morphology and composition were determined with physicochemical characterizations (TEM-EDS, XPS and XRD) and further bridged to their electrocatalytic activity. The electrochemical performances measured in rotating disk electrode experiments reached 7.68 ± 0.96 kA gmetal −1 for hydrazine electrooxidation at E = 0.4 V vs . RHE for the carbon-supported NiMo (9:1)/C. This value is amongst the highest reported in the literature. The large activity of the carbon-supported NiMo (9:1)/C catalyst was ascribed to the effect of a low but non-negligible (<15 at. %) molybdenum content, as molybdenum atoms stabilize the hydrazine N-N bond, thereby preventing the chemical decomposition of hydrazine into ammonia, and improving the catalyst selectivity towards the complete (and desired) hydrazine oxidation into N2 gas.